Archaeological survey in the territory of Diaguita Indigenous community from El Mollar, Tucumán, Argentina - Manasse, Bárbara; Vaqué, M. Lorena (Arqueología)
Nowadays, when “archaeological remains” are conceived in different parts of the world, as the cultural heritage of indigenous peoples, the indigenous community of El Mollar Diaguita raises the need to present the knowledge built together between archaeological (scientific) and indigenous (non-scientific) knowledge. To account for the existence of material evidence of the indigenous past/present is related to the intention of advancing on the explicit territorialization of community space. As a central objective of this paper we present archaeological information that form part of a cultural resource mapping process. First we discuss the conditions of the production of this research, in order to briefly introduce the indigenous community in its social, cultural and historical scenery, trying to provide information to foresee the difficulties of this proposal for the registration of Hispanic cultural materiality. We will explicit the latter, delving on its objectives and the methodology addressed, considering its theoretical and conceptual framework. As a third point, we evaluate existing scientific information in order to articulate/contrast it with the information developed as part of this survey work. Finally, we will make a few remarks on the obtained results, thinking about this particular context of the production.